Can vocal process granuloma location forecast the efficacy of anti-reflux treatment?. Issue 2 (9th February 2023) - Ding, J; Lou, Z
Abstract: Objective: The objective of this study was to evaluate the efficacy of anti-reflux therapy on the idiopathic vocal process granulomas. Method: This was a prospective case series study. The patients with vocal process granulomas who met the inclusion criteria were analysed. Proton pump inhibitors and vocal hygiene education were conducted for 8–20 weeks. Results: Of the 16 patients with vocal process granulomas, 5 (31.25 per cent) patients achieved complete remission. The complete remission rate of granulomas was not significantly related to age ( p = 1.000), sex ( p = 0.296), side ( p = 0.299), position ( p = 0.100), endoscopic morphology ( p = 0.263) or proton pump inhibitor treatment course ( p = 0.543) but was significantly associated with granuloma location ( p = 0.001) and granuloma size ( p = 0.012). Conclusion: Granulomas in the vocal cord and the margin of the vocal process had an excellent response to proton pump inhibitors, but granulomas on the surface of vocal process and arytenoid cartilage body had little response to proton pump inhibitors. The prolonged period of proton pump inhibitor treatment did not increase the complete remission rate of vocal process granulomas.